2006
DOI: 10.1080/01421590600969538
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of selection criteria for graduate students in radiation therapy

Abstract: Selection of suitable students into graduate medical and specialist health professional courses can be difficult. Historically, selection of students was primarily based on prior academic performance. Recently, however, more emphasis has been placed on considering broader academic backgrounds and personal characteristics and attitudes of students, but no reliable measurement tool is available to predict student success and satisfaction with their choice of profession. The aim of this study was to survey practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…For example, a number of studies in health care provide evidence that, in addition to skills and knowledge, certain personal characteristics contribute to successful clinical performance. 49,[57][58][59][60][61][62][63][64][65] Systematic development of a competent disaster medicine workforce requires first that worker competencies be defined and then validated. These competencies, then, could guide workforce development processes such as recruitment, assessment, selection and placement, training, and performance management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a number of studies in health care provide evidence that, in addition to skills and knowledge, certain personal characteristics contribute to successful clinical performance. 49,[57][58][59][60][61][62][63][64][65] Systematic development of a competent disaster medicine workforce requires first that worker competencies be defined and then validated. These competencies, then, could guide workforce development processes such as recruitment, assessment, selection and placement, training, and performance management.…”
Section: Discussionmentioning
confidence: 99%
“…These diverse attributes also span several general domains of knowledge, skills, attitudes, behaviors, and personal characteristics, domains consistently found in the general literature on competencies. For example, a number of studies in health care provide evidence that, in addition to skills and knowledge, certain personal characteristics contribute to successful clinical performance 49575859606162636465…”
Section: Discussionmentioning
confidence: 99%
“…4,5,6,7 There is some evidence that successful student selection may improve retention and promote long-term commitment to the radiography profession. 8,9,10,11 Radiography professionals' expertise focuses on the use of medically important diagnostic and therapeutic procedures when providing ionizing radiation to patients. 4,5,9,10,12,13 In addition to technical knowledge and skills, professionals must be able to engage appropriately and empathically with patients who are seriously ill. 4,5,9,10 The importance of problem-solving skills and ability to engage with other professionals has also been brought up by the professionals.…”
Section: Introductionmentioning
confidence: 99%
“…8,9,10,11 Radiography professionals' expertise focuses on the use of medically important diagnostic and therapeutic procedures when providing ionizing radiation to patients. 4,5,9,10,12,13 In addition to technical knowledge and skills, professionals must be able to engage appropriately and empathically with patients who are seriously ill. 4,5,9,10 The importance of problem-solving skills and ability to engage with other professionals has also been brought up by the professionals. 9,10 These requirements of the profession should be considered when planning student selection methods to select applicants with adequate knowledge and skills to study in radiography education.…”
Section: Introductionmentioning
confidence: 99%
“…1 Within the radiation therapy [MRT(T)] discipline, a survey amongst staff radiation therapists revealed that interpersonal traits were deemed necessary in the selection of graduate MRT(T) students, and included competencies that reflected attributes of empathy, excellent communications skills, and being a team player. 2 The interprofessional team promotes quality patient care, improves staff engagement, and increases organizational efficiency and innovation. 3 Radiation therapists routinely work in a team environment with their colleagues and members of other disciplines such as radiation oncologists, medical physicists, oncology nurses, and other allied health providers of the cancer treatment team.…”
mentioning
confidence: 99%